Revealing the Form of Directive Speech in Ready or Not Movie - Agiel Gendis Kun Hariani; Abdul Muhid; Puspita Dewi (Humanitatis : Journal of Language and Literature, 2021)
This research was done to reveal the dominant form of Directive Speech Act (DSA) usage in Ready or Not Movie by Guy Busick and R Christopher Murphy, which was released in 2019. To reveal the form of directive speech act used by some characters in the conversation, it was considered to use theory by Yule about the directive speech act, and the data were analyzed by using a qualitative descriptive method. This current research shows that there was 52 (fifty-two) form of directive speech act used in the movie. The detail forms were 29 (twenty-nine) or 55.7% command, 20 (twenty) or 38.4% requests, 5 (five) or 9.6% suggestions, and 3 (three) or 5.7% warnings. Therefore, it can be concluded that the dominant directive is the command. Keywords:Speech Acts, Directive Speech Acts,form of Directive, Movie